A Comparative Study of the Functional Outcome between Arthroscopic Capsular Release and Manipulation under Anesthesia with Hydrodilatation for Primary Adhesive Capsulitis of the Shoulder Joint: A Prospective Nonrandomized Study - Abind Josephchandran; Rajavel Kalirajan; Mohan Mahendramani (Journal of Orthopedics and Joint Surgery)
Introduction: Adhesive capsulitis, or frozen shoulder, poses challenges in effective treatment, with existing interventions exhibiting limitations. This study aims to compare arthroscopic capsular release (ACR) vs manipulation under anesthesia (MUA) with hydrodilatation for treating adhesive capsulitis, addressing uncertainties in management strategies. Objectives: The primary objective is to evaluate the efficacy of MUA with hydrodilatation vs ACR. Secondary objectives include assessing their impact on range of motion (ROM) improvement and determining which intervention provides superior early pain relief. Materials and methods: This prospective nonrandomized study, conducted at SRM Medical College, Hospital and Research Centre, involves 102 participants meeting inclusion criteria. Patients aged 40–65 years with primary adhesive capsulitis undergo either ACR (group A) or MUA with hydrodilatation (group B). Data collected from August 2022 to December 2024 include clinical history, radiological examinations, shoulder pain and disability index (SPADI), and University of California—Los Angeles (UCLA) scores. Convenience sampling was employed to allocate patients to intervention groups, with participants selected based on accessibility and willingness to participate in the study. Results: Demographic characteristics and baseline scores show comparable distributions across both groups. ACR demonstrates significant improvement in abduction, cross-body adduction, forward flexion, internal and external rotation at various follow-up intervals (p < 0.05). SPADI, UCLA, and visual analog scale (VAS) scores consistently show statistically significant improvements in the ACR group (p < 0.001). Postoperative satisfaction is notably higher with ACR (p < 0.01). Conclusion: The study concludes that ACR yields superior early outcomes in terms of ROM improvement, pain relief, and patient satisfaction compared to MUA with hydrodilatation for adhesive capsulitis. While both interventions show improvement, ACR consistently exhibits better results across multiple parameters and follow-up intervals, providing valuable insights for clinicians.